Adaptive control strategy for power output stability in long-time operation of fuel cells. (1st January 2022) - Yang, Qinwen; Gao, Bin; Cheng, Qiang; Xiao, Gang; Meng, Min
Abstract: An adaptive control strategy is developed for active degradation compensation of fuel cells, so as to improve output performance stability during long-time operation. Two groups of long-time tests of DMFC under different operating parameters are designed and implemented. The parameter adjustment significance that defines the adjusting priority is obtained from experimental analyses, based on which, the adaptive control strategy is developed and systematically tested. The results show that temporary degradation and permanent degradation for fuel cell performance could be differentiated in the process of performance degradation and recovery. The operation condition which would bring a higher energy conversion efficiency may lead to more serious degradations. The developed control strategy could help to adaptively alleviate fuel cell degradation during long-time operation. The temporary degradation and permanent degradation rates both decreased in daily operation, and the errors between output voltage and objective values are controlled within 2 %. The study provides an effective reference for improving the fuel cell stability during long-time operation and prolonging its service life. Highlights: An adaptive control strategy is developed for active degradation compensation of fuel cells. The output performance stability during long-time operation has been improved. The strategy could help to adaptively alleviate fuel cell degradation during long-time operation. The study provides an effective reference for prolonging the service life of the fuel cell.